From silk to silicon : - Garten, Jeffrey E.
The story of globalization, the most powerful force in history, as told through the life and times of ten people who changed the world by their singular, spectacular accomplishments. This is the first book to look at the history of globalization through the lens of individuals who did something transformative, as opposed to describing globalization through trends, policies, or particular industries. From Silk to Silicon tells the story of who these men and women were, what they did, how they did it and how their achievements continue to shape our world today.